2014
DOI: 10.1017/s1368980014000457
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in minority populations

Abstract: Objective: Black and Hispanic individuals synthesize less vitamin D per unit of sun exposure than white individuals. The relationship between UV radiation and vitamin D insufficiency in minorities has not been well explored. Design: Prospective cohort study. Setting: Using the National Health and Nutrition Examination Survey, we obtained serum vitamin D levels for non-Hispanic Whites, Hispanics and non-Hispanic Blacks aged ≥18 years from [2000][2001][2002][2003][2004][2005][2006]. We linked these data with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
0
22
1
Order By: Relevance
“…Increasing fruit and vegetable consumption may also improve the status of other micronutrients, such as vitamins A and B6 [ 79 ]. More consideration should be paid to the risk of vitamin D deficiency in minority populations [ 80 ]. Educational interventions to increase vitamin D status may be only marginally effective; food fortification may be more appropriate [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing fruit and vegetable consumption may also improve the status of other micronutrients, such as vitamins A and B6 [ 79 ]. More consideration should be paid to the risk of vitamin D deficiency in minority populations [ 80 ]. Educational interventions to increase vitamin D status may be only marginally effective; food fortification may be more appropriate [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of patient setting showed that most of the study populations included HIV/HCV coinfected African Americans. How race affects the impact of vitamin D on bone health has recently been investigated in African American men and women, revealing differences due to socioeconomic and genetic factors, such as resistance to the bone resorbing effects of PTH in the black population [ 33 , 40 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the selected articles reveal some aspects that prompt us to reconsider the definition of hypovitaminosis D. In fact, the significance of vitamin D deficiency has several limitations because 25-hydroxyvitamin D concentrations varied by age, season, study sample size, and methodological assay approach [25(OH)D assay used] [ 37 , 39 , 40 ]. Moreover, black and Hispanic individuals synthesize less vitamin D per unit of sun exposure than white individuals [ 33 , 41 , 42 ]. Therefore, levels of vitamin D in HIV/HCV coinfected patients should be monitored according to the reference range for the sample setting.…”
Section: Discussionmentioning
confidence: 99%
“…Our recommendation is to expeditiously screen groups known to have both disproportionately high rates of severe COVID-19 relative to their population percentages and vitamin D de ciency. Up to 40% of African Americans are suspected to be vitamin D de cient at random seasonal testing [10] but this percentage that may reach 65 % in winter months [27]. Native Americans have been infrequently evaluated for their 25VD status but a report from Oklahoma found that two-thirds of apparently healthy individuals had 25VD below 20 ng/dL [9].…”
Section: Discussionmentioning
confidence: 99%